2016
DOI: 10.1155/2016/6345656
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Promotes Expression of Matrix Metalloproteinase 13 through NF-κB Signaling in Osteoarthritis

Abstract: Osteopontin (OPN) is associated with the severity and progression of osteoarthritis (OA); however, the mechanism of OPN in the pathogenesis of OA is unknown. In this study, we found that OA patients had higher abundance of OPN and matrix metalloproteinase 13 (MMP13). In chondrocytes, we showed that OPN promoted the production of MMP13 and activation of NF-κB pathway by increasing the abundance of p65 and phosphorylated p65 and translocation of p65 protein from cytoplasm to nucleus. Notably, inhibition of NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…Cartilage degeneration is the main feature of OA, and OPN is a secreted multifunctional phosphoprotein involved in the molecular pathogenesis of OA by contributing to progressive degeneration of articular cartilage [11]. In the present study, our results confirmed that the expression of OPN mRNA in human OA cartilage chondrocytes was enhanced compared with that in normal cartilage chondrocytes [7,26].…”
Section: Discussionsupporting
confidence: 84%
“…Cartilage degeneration is the main feature of OA, and OPN is a secreted multifunctional phosphoprotein involved in the molecular pathogenesis of OA by contributing to progressive degeneration of articular cartilage [11]. In the present study, our results confirmed that the expression of OPN mRNA in human OA cartilage chondrocytes was enhanced compared with that in normal cartilage chondrocytes [7,26].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, mRNA expression and protein abundance of OPN are associated with the pathogenesis of OA [42]. Pullig et al had demonstrated that the SPP1 mRNA isolated from human OA cartilage is elevated compared to normal cartilage samples [46].…”
Section: Impact Of Vibration On Osteopontinmentioning
confidence: 99%
“…Adipose tissue of obese individuals produces elevated amounts of numerous mediators of inflammation [ 70 , 71 , 72 ]. Articular cartilage matrix tissue destruction by metalloproteinases, observed in OA, may result from chronic activation of obesity-induced pro-inflammatory intracellular signaling in joints [ 73 , 74 , 75 ]. A set of clinical studies demonstrated curcumin, curcuminoid, and curcumin-based therapeutics to improve the extremity function and reduce pain and treatment in OA patients [ 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%